The Genesis of Article 234 of the UNCLOS - Solski, Jan Jakub (Ocean Development & International Law, 2021)
Article 234 is exceptional regarding its wording and placement in the United Nations Convention on the Law of the Sea (UNCLOS), as well as in its historical background. The Arctic provision has given rise to divergent interpretations regarding the conditions for invoking it, the limitations on the authority under Article 234, and its spatial scope of application. It has served as a justification for specific legislation adopted by Canada and Russia that has been opposed by the United States. The article, describes as a “textbook example of finding a compromise in international treaty negotiations,” was negotiated directly and privately, among these three states during the Third United Nations Conference on the Law of the Sea (UNCLOS III). This article describes the historical background to Article 234 and sheds new light on the negotiating process that led to the adoption of the provision.